The role of community benefits agreements for community development, social justice adult education, and program planning - Kayla Savage; Susan Yelich Biniecki (Adult Education Research Conference, 2017)
The purpose of this roundtable is to facilitate discussion and debate about the role of community benefits agreements in community development, social justice education, and program planning within community development contexts.
Keywords: community benefits agreements; social justice education; program planning; community development